Pemanfaatan Terak Tanur Tinggi dari Hasil Pembakaran Bata Merah Desa Bogor Cawas Klaten Sebagai Bahan Tambah dan Kapur Tohor Sebagai Pengganti Semen Untuk Campuran Beton - Yuliaritno, Eko; , Ir. H. Suhendro Trinugroho, M.T; , Basuki, S.T, M.T (2015)
Concrete is a mixture of cement, coarse aggregate, fine aggregate, water and material can also be added which will vary greatly on a certain percentage in order to function better and more economical. The addition of slag blast furnace from the burning red brick (TBM) which is mashed as an ingredient added to the concrete mix is ​​expected to be one of the alternatives are quite good and the provision of quicklime as a substitute for cement is intended to become the connective important and widely used in the physical development of concrete , The purpose of this study was to determine differences in compressive strength, tensile strength and flexural strength concrete resulting from the addition of blast furnace slag from the burning red brick with adhesive cement or cement and quicklime. Percentage variation of the addition of blast furnace slag powder from the burning red brick is 0%, 5%, 7.5%, 10%, 12.5%, 15% by weight of cement, and the percentage of calcium oxide is 25% by weight of cement as a substitute partly cement. The total number of concrete specimen there are 36 pieces, 24 pieces in the form of concrete cylinders with a diameter of 15 cm and 30 cm high and 12 pieces in the form of concrete beams with a length of 60 cm, height 20 cm and width 10 cm. Concrete is not reinforced and the tests performed are testing concrete compressive strength, tensile strength and flexural strength of concrete sides of the concrete after 28 days, mix design using Road Note no.4. From the test results of compressive strength of normal concrete using cement adhesive is 18.108 MPa, with the addition of powder TBM 12.5% ​​yield maximum compressive strength of 27,954 MPa, so that an increase of 35.223%. The compressive strength of normal concrete using adhesive cement and quicklime amounted to 25% of the weight of cement is 13.807 MPa, with the addition of 10% TBM produces maximum compressive strength of 22.125 MPa, so that an increase of 37.596%. Testing the tensile strength of normal concrete sides using adhesive cement is 6.889 MPa, with the addition of powder TBM 12.5% ​​yield maximum tensile strength divided by 10.044 MPa, so that an increase of 31.416%. The value of tensile strength of normal concrete sides using adhesive cement and quicklime amounted to 25% of the weight of cement is 5.822 MPa, with the addition of 5% powder TBM produces maximum tensile strength of 8.4 MPa sides, so an increase of 30 668%. Testing of flexural strength of normal concrete using cement adhesive is 5773 MPa, with the addition of 15% TBM powder produces a maximum flexural strength of 6.227 MPa, so that an increase of 7.301%. The value of flexural strength of normal concrete using adhesive cement and quicklime amounted to 25% of cement weight is 2,971 MPa, with the addition of powder TBM 12.5% ​​yield maximum flexural strength of 6.042 MPa, so that an increase of 50.825%.